2023
DOI: 10.3390/ijerph20065047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the N-hexanoyl-L-homoserine Lactone on the Carbon Fixation Capacity of the Algae–Bacteria System

Abstract: Algae–bacteria systems are used widely in wastewater treatment. N-hexanoyl-L-homoserine lactone (AHL) plays an important role in algal-bacteria communication. However, little study has been conducted on the ability of AHLs to regulate algal metabolism and the carbon fixation ability, especially in algae–bacteria system. In this study, we used the Microcystis aeruginosa + Staphylococcus ureilyticus strain as a algae–bacteria system. The results showed that 10 ng/L C6-HSL effectively increased the chlorophyll-a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…The premise of exploring exogenous AHLs function is that these AHLs produced by other organisms can affect Microcystis. Yan et al found that the addition of 3-OH-C4-HSL extracted from bacterial sludge could promote microalgal growth, alike to the function of endogenous AHLs [41], whereas Xue et al found that exogenous AHLs addition decreased Microcystis growth rate [62]. Based on numerous studies, exogenous AHLs affect Microcystis in several aspects alike to endogenous AHLs.…”
Section: Regulatory Effects Of Exogenous Ahlsmentioning
confidence: 99%
See 3 more Smart Citations
“…The premise of exploring exogenous AHLs function is that these AHLs produced by other organisms can affect Microcystis. Yan et al found that the addition of 3-OH-C4-HSL extracted from bacterial sludge could promote microalgal growth, alike to the function of endogenous AHLs [41], whereas Xue et al found that exogenous AHLs addition decreased Microcystis growth rate [62]. Based on numerous studies, exogenous AHLs affect Microcystis in several aspects alike to endogenous AHLs.…”
Section: Regulatory Effects Of Exogenous Ahlsmentioning
confidence: 99%
“…This suggested that even the same exogenous AHLs analogs may pose opposite effects on EPSs and MCs secretion [28]. In aspect of nutrition/energy metabolism activities, a part of exogenous AHLs can change relative genes expression and enzymes activities to regulate metabolic processes such as carbon/nitrogen metabolism in Microcystis [28,62,63]. C6-HSL can increase carbon sequestration efficiency to promote Microcystis growth [62].…”
Section: Regulatory Effects Of Exogenous Ahlsmentioning
confidence: 99%
See 2 more Smart Citations
“…In insects, this chemosensing process is involved in prey-seeking behavior (Cummins et al, 2014), whereas in vertebrates, it is involved in taste perception (Chandrashekar et al, 2009), lung function (Kunert et al, 2022), and the control of immunity (Strowitzki et al, 2022). In algae, aquatic plants, diatoms, and cyanobacteria, CO 2 /bicarbonate sensing is highly relevant in order to supply sufficient CO 2 for photosynthesis, and hence, sophisticated carbon-concentrating mechanisms have independently evolved in many such organisms (Momayyezi et al, 2020;Santhanagopalan et al, 2021;Zhang et al, 2022;Liao et al, 2023;Shimakawa et al, 2023).…”
Section: Co 2 /Bicarbonate Sensingmentioning
confidence: 99%